Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1371/journal.pone.0005775
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Lymphoblasts from Autistic and Nonaffected Sib Pairs: Altered Pathways in Neuronal Development and Steroid Biosynthesis

Abstract: Despite the identification of numerous autism susceptibility genes, the pathobiology of autism remains unknown. The present “case-control” study takes a global approach to understanding the molecular basis of autism spectrum disorders based upon large-scale gene expression profiling. DNA microarray analyses were conducted on lymphoblastoid cell lines from over 20 sib pairs in which one sibling had a diagnosis of autism and the other was not affected in order to identify biochemical and signaling pathways which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 99 publications
(114 reference statements)
6
124
0
Order By: Relevance
“…If retinoids modulate CD38 transcription in the brain, which in turn mediates oxytocin release, then the relationship we have shown [72] between cognitive function and CD38 mRNA levels in LBC cells may be reflecting common state characteristics of OT-CD38-RA pathways in different tissues. Indeed, various studies have employed LBC lines to model brain dysfunctions in autism [90][91][92] and other neuropsychiatric disorders [93][94][95][96][97].…”
Section: Link Between Cd38 Expression and Clinical Characteristics Inmentioning
confidence: 99%
See 1 more Smart Citation
“…If retinoids modulate CD38 transcription in the brain, which in turn mediates oxytocin release, then the relationship we have shown [72] between cognitive function and CD38 mRNA levels in LBC cells may be reflecting common state characteristics of OT-CD38-RA pathways in different tissues. Indeed, various studies have employed LBC lines to model brain dysfunctions in autism [90][91][92] and other neuropsychiatric disorders [93][94][95][96][97].…”
Section: Link Between Cd38 Expression and Clinical Characteristics Inmentioning
confidence: 99%
“…Most of the studies to date have focused on human lymphocytes gene expression profiling, comparison between illness groups and normal controls, and cross-matching with human postmortem brain gene expression data. A number of studies have specifically examined gene expression patterns in ASD [90][91][92][114][115][116][117][118][119][120][121][122][123]. It should be noted that predating this gush of expression studies in ASD, hyperserotonemia was observed in one third of patients and platelet serotonin was suggested as a marker for this disorder [124][125][126][127].…”
Section: Biomarkers For Autism Spectrum Disordersmentioning
confidence: 99%
“…GWAS identified a number of chromosomal regions to have linkage to autism, including the region 3p25, where ATP2B2 (as well as a number of other genes) is located (200,235,341). In a subsequent study comparing the gene expression profiles of lymphoblasts from autistic and nonaffected sibling pairs, ATP2B2 was the only gene found to be differentially expressed of the 43 known genes in the identified region at 3p25 (164). Using Ingenuity Pathway Analysis, Hu et al (164) identified that differential expression of ATP2B2 may affect nervous system development and function via altering Purkinje cell morphology, cerebellar development, or synapse biogenesis.…”
Section: B Pmca2 Hereditary Deafness and Autismmentioning
confidence: 99%
“…In a subsequent study comparing the gene expression profiles of lymphoblasts from autistic and nonaffected sibling pairs, ATP2B2 was the only gene found to be differentially expressed of the 43 known genes in the identified region at 3p25 (164). Using Ingenuity Pathway Analysis, Hu et al (164) identified that differential expression of ATP2B2 may affect nervous system development and function via altering Purkinje cell morphology, cerebellar development, or synapse biogenesis. Intracellular Ca 2ϩ levels and Ca 2ϩ -signaling pathways are indeed important in the regulation of neuronal survival, differentiation, migration, and synaptogenesis, and it is likely that perturbations in these processes may play a role in the pathogenesis of autism spectrum disorders (193 spectrum disorders in Italian families and in those of Han Chinese descent (296, 414).…”
Section: B Pmca2 Hereditary Deafness and Autismmentioning
confidence: 99%
“…Because little was known about specific genes that are differentially methylated in ASD, Nguyen et al used an unbiased approach to investigate DNA methylation differences in LCL from discordant twin and sib pairs, where one individual of each pair had been diagnosed with idiopathic ASD [70]. Global methylation was assessed using an 8K CpG island array and the resulting data was compared against previously obtained gene expression data [71,72] for the same samples. Functional analysis of genes that exhibited both increased methylation and decreased expression revealed a gene interaction network that included ASD-relevant processes, such as fetal development, regulation of synapse, mental deficiency, inflammation, digestion, and steroid biosynthesis (Fig.…”
Section: The Potential Of Ncrnas As Biomarkers For Asdmentioning
confidence: 99%